CATECHIN CONTENT AND ANTIOXIDANT ACTIVITY OF SOME BREWED TEMPERATURE OF BLACK TEA SYRUP - Tuty Anggraini (Institution for Industrial Research and Standardization of Industry - Padang, 2011)
The catechin contents and the antioxidant activity of black tea syrup that brewed at some temperature still poorly understood. It has been investigated whether catechin contents and antioxidant activity of black tea syrup may be affected by hot or cold water. The temperature of 30°C, 60°C, and 90°C were used to brew the syrup, and then the catechin and the antioxidant were determined at each temperature by using DPPH radical scavenging activity method. Measurement of DPPH was conducted for 2 minutes reaction time. Catechin contents were determined by using HPLC method. The result of research showed that the catechin and the antioxidant activity affected by temperature tested. Five kinds of catechin derivatives detected in black tea syrup, EGC (epigallocatechin), C (catechin), EGCG (epigallocatechin gallate), EC (epicatechin) and ECG (epicatechin gallate). The highest DPPH scavenging activity of black tea syrup was showed by 30°C.ABSTRAKKandungan katechin dan aktivitas antioksidan dari sirup teh hitam yang diseduh pada beberapa temperatur masih belum begitu dipahami. Pada penelitian ini telah diselidiki apakan kandungan katechin dan aktioksidan dipengaruhi oleh air dingin atau air panas. Temperatur 30oC, 60oC, dan 90oC digunakan untuk menyeduh sirup teh hitam lalu ditentukan kandungan katechin dan aktifitas antioksidannya pada masing-masing temperatur menggunakan metode aktifitas perangkap radikal bebas DPPH (dyphenyl pycrylhydrazyl). Pengukuran DPPH dilakukan selama waktu reaksi dua menit. Kandungan katechin ditentukan menggunakan metode HPLC (High Performance Liquid Chromatography). Hasil penelitian menunjukkan bahwa kandungan katechin dan aktifitas antioksidan sirup teh hitam dipengaruhi oleh temperatur yang diuji. Lima jenis turunan katechin terdeteksi dalam sirup teh hitam yaitu EGC (epigallocatechin), C (catechin), EGCG (epigallocatechin gallate), EC (epicatechin) and ECG (epicatechin gallate). Aktifitas perangkap DPPH tertinggi dari sirup teh hitam diperoleh pada temperatur 30oC.